2010
DOI: 10.3238/arztebl.2010.0809
|View full text |Cite
|
Sign up to set email alerts
|

Physical Performance in Middle Age and Old Age

Abstract: Performance losses in middle age are mainly due to a sedentary lifestyle, rather than biological aging. The large contingent of older "newcomers" among marathon runners demonstrates that, even at an advanced age, non-athletes can achieve high levels of performance through regular training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…Therefore, all physiological parameters discussed earlier would not impact running performance in ultra-marathon distances as suggested by other authors [1,40-43]. Leyk et al [54] found performance losses in middle age mainly to be due to a sedentary lifestyle, rather than biological aging. They showed that decline in performance was not related to age until the age of 55 years.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, all physiological parameters discussed earlier would not impact running performance in ultra-marathon distances as suggested by other authors [1,40-43]. Leyk et al [54] found performance losses in middle age mainly to be due to a sedentary lifestyle, rather than biological aging. They showed that decline in performance was not related to age until the age of 55 years.…”
Section: Discussionmentioning
confidence: 73%
“…Apart from marathon running in a city marathon, athletes can also compete in mountain marathons ( http://www.mountainrunning.com , http://www.wmra.info ). However, in contrast to city marathons (Jokl et al 2004 , Lepers and Cattagni 2012 , Leyk et al 2007 , 2009 , 2010 ) we have no data on the participation and performance trends in age group mountain marathoners. Since mountain running is of increasing popularity ( http://www.mountainrunning.com , http://www.wmra.info ), the aim of this study was to investigate participation and performance trends in age group marathoners competing in the ‘Jungfrau Marathon’ held in the Swiss Alps.…”
Section: Introductionmentioning
confidence: 82%
“…Marathon running is of high popularity where marathon races are mainly held as city marathons in large cities (Jokl et al 2004 ; Lepers and Cattagni 2012 ; Leyk et al 2007 , 2009 , 2010 ). Participation and performance trends in elite and age group city marathoners are well investigated (Ahmadyar et al 2015 ; Anthony et al 2014 ; Aschmann et al 2013 ; Cribari et al 2013 , Jokl et al 2004 , Lepers and Cattagni 2012 ; Leyk et al 2007 , 2009 ), but very little is known for mountain marathoners (Zingg et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that age [1-6], sex [2,4-7], training [2,4,8], anthropometry [2,4,8] and nationality [9] were crucial determining factors for long-distance running performance.…”
Section: Introductionmentioning
confidence: 99%